Lipid Lowering Activity and Free Radical Scavenging Effect of Cinnamomum tamala (Fam: Lauraceae) - Al-Mamun, R; Hamid, A; Islam, MK; Chowdhury, JA; Azam, ATM Zafrul (International Journal of Natural Sciences, 2012)
Lipid profile is a blood test that measures the amount of lipids, or fats, in your blood. The lipids measured are usually total cholesterol, HDL-C, LDL-C and triglycerides. When levels of these lipids are abnormal, there is an increased risk of heart attack and stroke. In our study, we use methanol crude extract for lipid lowering activity on rabbit and found that lipid profile was reduced by 14.0, 1.0, 4.0 and 15.0 mg/dl for total cholesterol, HDL-C, LDL-C and triglyceride respectively after using the plant extract (dose 500mg/rabbit for 10 days); where atorvastatin (0.005mg/rabbit) was used as standard lipid lowering agent. We also focused on the antioxidant property of crude methanol extract. Here we also carried out free radical-scavenging activity study and found the IC50 value for C. tamala is 6.00 μg/ml where the standard antioxidant (ascorbic acid) gave the value of 3.21μg/ml. DOI: http://dx.doi.org/10.3329/ijns.v1i4.9735 IJNS 2011 1(4): 93-96